THE IMPORTANCE OF THE SPOILER IN AUTOMOTIVE AERODYNAMICS (Journal of Multidisciplinary Sciences and Innovations, 2025)
Aerodynamic efficiency is essential in modern vehicle design, contributing significantly to fuel economy, stability, and high-speed performance. Spoilers are one of the most widely used aerodynamic components, primarily aimed at reducing lift and managing airflow over the vehicle. This study investigates the aerodynamic role of spoilers on passenger cars by analyzing their effect on drag coefficient, lift force, and stability. Using wind tunnel testing and computational simulations, the paper compares vehicles with and without spoilers under various conditions. The results reveal that properly designed spoilers can reduce aerodynamic lift by over 25% and improve overall vehicle control at high speeds. The research also highlights the interrelationship between spoiler geometry, airflow behavior, and vehicle dynamics.